The potential role of epigenetics on multipotent cell differentiation capacity of mesenchymal stromal cells - Yannarelli, Gustavo Gabriel (2013)
Human umbilical cord perivascular cells (HUCPVCs) are a readily available source of mesenchymal stromal cells (MSCs) for cell therapy. We were interested in understanding how differences from human bone marrow (BM)-derived MSCs might yield insights into MSC biology. We found that HUCPVCs exhibited increased telomerase activity and longer telomeres compared with BM-MSCs. We also observed enhanced expression of the pluripotency factors OCT4, SOX2, and NANOG in HUCPVCs. The methylation of OCT4 and NANOG promoters was similar in both cell types, indicating that differences in the expression of pluripotency factors between the MSCs were not associated with epigenetic changes. MSC methylation at these loci is greater than reported for embryonic stem cells but less than in dermal fibroblasts, suggesting that multipotentiality of MSCs is epigenetically restricted. These results are consistent with the notion that the MSC population (whether BM- or HUCPV-derived) exhibits higher proliferative capacity and contains more progenitor cells than do dermal fibroblasts.